Arduino up and running - Jepson, Brian, 1967- (Make: projects., 2010)
"Build fun and creative electronic projects with Arduino, the open source prototyping platform that's taken the design and hobbyist world by storm. In 90 minutes of video, you'll get a complete overview of basic electronics and the Arduino microcontroller and software. Then you'll follow hands-on lessons on how to write simple Arduino programs that interact with various electronic components. This easy-to-follow tutorial is ideal for designers, artists, hackers, makers, and anyone interested in creating sensor-based systems"--Resource description page (viewed Jan. 20, 2011).